2016
DOI: 10.5603/kp.a2015.0210
|View full text |Cite
|
Sign up to set email alerts
|

Potassium channel changes of peripheral blood T-lymphocytes from Kazakh hypertensive patients in Northwest China and the inhibition effect towards potassium channels by telmisartan

Abstract: A b s t r a c tBackground and aim: Increasing evidence indicates that chronic inflammation is a direct or indirect manifestation of hypertension. Potassium channels are thought to be critical for lymphocyte activation, which suggests that hypertension may be an inflammatory disease initiated at the ion channel level. Methods:This study investigated changes in interleukin (IL)-6, IL-17, and transforming growth factor beta (TGF-b1) expression in the blood of Kazakh hypertensive patients in Northwest China using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…However, healthy subjects were not enrolled and circulating Th17 levels were not measured in this study [7]. Consistent with these results, many clinical studies have found that circulating IL-17 levels significantly increased in hypertensive patients [13, 14]. Moreover, Yao et al found that serum IL-17 levels were significantly higher in subjects with prehypertension, defined as systolic BP of 120 to 139 mm Hg or diastolic BP of 80 to 89 mm Hg, than in subjects with optimal BP, defined as systolic BP < 120 mm Hg and diastolic BP < 80 mm Hg [31].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…However, healthy subjects were not enrolled and circulating Th17 levels were not measured in this study [7]. Consistent with these results, many clinical studies have found that circulating IL-17 levels significantly increased in hypertensive patients [13, 14]. Moreover, Yao et al found that serum IL-17 levels were significantly higher in subjects with prehypertension, defined as systolic BP of 120 to 139 mm Hg or diastolic BP of 80 to 89 mm Hg, than in subjects with optimal BP, defined as systolic BP < 120 mm Hg and diastolic BP < 80 mm Hg [31].…”
Section: Discussionsupporting
confidence: 57%
“…Data from previous studies revealed that medication use effectively regulates Teff cell activity [5, 6, 11, 14, 20]. Therefore, we analyzed the effect of prehospital medication on effector T cell activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different types of cardiovascular diseases (CVD) are identified after analysing the accumulated relevant articles, as depicted in Figure 2 . These CVD types are classified into six categories including coronary heart disease [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], heart failure [ 22 , 26 , 30 , 31 , 32 , 33 , 34 ], arrhythmia [ 29 , 33 , 35 , 36 , 37 , 38 , 39 ], aortic diseases [ 25 , 26 , 29 , 40 , 41 ], and cardiomyopathy [ 26 , 29 , 33 , 42 , 43 ], and only one study for hypertension (HTN) [ 44 ]. Among these finalised 28 articles, the most represented category is coronary heart disease ( n = 14).…”
Section: Resultsmentioning
confidence: 99%
“…The pipette solution contained 150.0 mM KCl, 1.0 mM CaCl 2 , 1.0 mM MgCl 2 , 10.0 mM HEPES, and 10.0 mM K 2 EGTA (pH 7.20, adjusted with KOH). The perfusing solution contained 150.0 mM NaCl, 4.5 mM KCl, 1.0 mM CaCl 2 , 1.0 mM MgCl 2 , and 10.0 mM HEPES (pH 7.35, adjusted by NaOH), and Kv1.3 currents were elicited with voltage ramps from -80 to +40 mV of 300-ms duration applied every 30 s, as described previously ( Zhao et al, 2014 ; Zhang et al, 2016 ). Fast and slow capacitances were compensated before every recording.…”
Section: Methodsmentioning
confidence: 99%